62.6k views
0 votes
What is X^3-2X^2+5/4X^2-3

User Fvrab
by
5.2k points

1 Answer

6 votes

Answer:

X = ((56 sqrt(3) + 97)^(2/3) + 1)/(4 (56 sqrt(3) + 97)^(1/3)) + 1/4 or X = ((-1)^(2/3) - (-1)^(1/3) (56 sqrt(3) + 97)^(2/3))/(4 (56 sqrt(3) + 97)^(1/3)) + 1/4 or X = 1/4 ((-1)^(2/3) (97 + 56 sqrt(3))^(1/3) - (56 sqrt(3) - 97)^(1/3)) + 1/4

Explanation:

Solve for X:

X^3 - (3 X^2)/4 - 3 = 0

Bring X^3 - (3 X^2)/4 - 3 together using the common denominator 4:

1/4 (4 X^3 - 3 X^2 - 12) = 0

Multiply both sides by 4:

4 X^3 - 3 X^2 - 12 = 0

Eliminate the quadratic term by substituting x = X - 1/4:

-12 - 3 (x + 1/4)^2 + 4 (x + 1/4)^3 = 0

Expand out terms of the left hand side:

4 x^3 - (3 x)/4 - 97/8 = 0

Divide both sides by 4:

x^3 - (3 x)/16 - 97/32 = 0

Change coordinates by substituting x = y + λ/y, where λ is a constant value that will be determined later:

-97/32 - 3/16 (y + λ/y) + (y + λ/y)^3 = 0

Multiply both sides by y^3 and collect in terms of y:

y^6 + y^4 (3 λ - 3/16) - (97 y^3)/32 + y^2 (3 λ^2 - (3 λ)/16) + λ^3 = 0

Substitute λ = 1/16 and then z = y^3, yielding a quadratic equation in the variable z:

z^2 - (97 z)/32 + 1/4096 = 0

Find the positive solution to the quadratic equation:

z = 1/64 (97 + 56 sqrt(3))

Substitute back for z = y^3:

y^3 = 1/64 (97 + 56 sqrt(3))

Taking cube roots gives 1/4 (97 + 56 sqrt(3))^(1/3) times the third roots of unity:

y = 1/4 (97 + 56 sqrt(3))^(1/3) or y = -1/4 (-97 - 56 sqrt(3))^(1/3) or y = 1/4 (-1)^(2/3) (97 + 56 sqrt(3))^(1/3)

Substitute each value of y into x = y + 1/(16 y):

x = 1/(4 (56 sqrt(3) + 97)^(1/3)) + 1/4 (56 sqrt(3) + 97)^(1/3) or x = (-1)^(2/3)/(4 (56 sqrt(3) + 97)^(1/3)) - 1/4 (-56 sqrt(3) - 97)^(1/3) or x = 1/4 (-1)^(2/3) (56 sqrt(3) + 97)^(1/3) - 1/4 ((-1)/(56 sqrt(3) + 97))^(1/3)

Bring each solution to a common denominator and simplify:

x = ((56 sqrt(3) + 97)^(2/3) + 1)/(4 (97 + 56 sqrt(3))^(1/3)) or x = ((-1)^(2/3) - (-1)^(1/3) (56 sqrt(3) + 97)^(2/3))/(4 (97 + 56 sqrt(3))^(1/3)) or x = 1/4 ((-1)^(2/3) (56 sqrt(3) + 97)^(1/3) - (56 sqrt(3) - 97)^(1/3))

Substitute back for X = x + 1/4:

Answer: X = ((56 sqrt(3) + 97)^(2/3) + 1)/(4 (56 sqrt(3) + 97)^(1/3)) + 1/4 or X = ((-1)^(2/3) - (-1)^(1/3) (56 sqrt(3) + 97)^(2/3))/(4 (56 sqrt(3) + 97)^(1/3)) + 1/4 or X = 1/4 ((-1)^(2/3) (97 + 56 sqrt(3))^(1/3) - (56 sqrt(3) - 97)^(1/3)) + 1/4

User Ankit
by
4.4k points